Diesel Engine Exhaust Initiates a Sequence of Pulmonary and Cardiovascular Effects in Rats. (3rd October 2010) - Kooter, Ingeborg M.; Gerlofs-Nijland, Miriam E.; Boere, A. John F.; Leseman, Daan L. A. C.; Fokkens, Paul H. B.; Spronk, Henri M. H.; Frederix, Kim; ten Cate, Hugo; Knaapen, Ad M.; Vreman, Hendrik J.; Cassee, Flemming R.
Abstract : This study was designed to determine the sequence of events leading to cardiopulmonary effects following acute inhalation of diesel engine exhaust in rats. Rats were exposed for 2 h to diesel engine exhaust (1.9 mg/m 3 ), and biological parameters related to antioxidant defense, inflammation, and procoagulation were examined after 4, 18, 24, 48, and 72 h. This in vivo inhalation study showed a pulmonary anti-oxidant response (an increased activity of the anti-oxidant enzymes glutathione peroxidase and superoxide dismutase and an increase in heme oxygenase-1 protein, heme oxygenase activity, and uric acid) which precedes the inflammatory response (an increase in IL-6 and TNF-α ). In addition, increased plasma thrombogenicity and immediate anti-oxidant defense gene expression in aorta tissue shortly after the exposure might suggest direct translocation of diesel engine exhaust components to the vasculature but mediation by other pathways cannot be ruled out. This study therefore shows that different stages in oxidative stress are not only affected by dose increments but are also time dependent.